2021
DOI: 10.1038/s41598-021-93525-w
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical composition and antioxidant properties of methanolic extracts of whole and dehulled Bambara groundnut (Vigna subterranea) seeds

Abstract: The distribution of phytochemicals and their contribution to antioxidant potentials in whole and dehulled Bambara groundnut (BGN) seeds was evaluated. Whole BGN seeds were sorted using the testa and hilium colour and further grouped into whole and dehulled BGN seeds. Extractions of both whole and dehulled BGN seeds was done using methanol and the extracts assayed for total phenolics (TPC), flavanol, flavonol, anthocyanin content, oxygen radical absorbance capacity (ORAC) and ferric reducing antioxidant power (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Many of these components have antioxidant properties, and a clear correlation between antioxidant properties and colour of the seed coat has been demonstrated (e.g., in cowpea seed coat [ 69 , 70 ]). Adedayo et al [ 71 ] found that the more colourful seeds of Vigna subterranea have greater antioxidant capacity. In Phaseolus vulgaris, antioxidant capacity is higher in beans with dark seed coats, in which phenolic compounds and flavonoids were found in higher quantities [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many of these components have antioxidant properties, and a clear correlation between antioxidant properties and colour of the seed coat has been demonstrated (e.g., in cowpea seed coat [ 69 , 70 ]). Adedayo et al [ 71 ] found that the more colourful seeds of Vigna subterranea have greater antioxidant capacity. In Phaseolus vulgaris, antioxidant capacity is higher in beans with dark seed coats, in which phenolic compounds and flavonoids were found in higher quantities [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Significant levels of alkaloids, flavonoid conjugates (including epicatechin, catechin, [21] quercetin, kaempferol, apigenin, glycosides), saponins, steroids, triterpenoids, phenols, anthocyanins and carotenoids have also been reported [22,23,24]. The highest concentration of tannins and flavonoids have been found in red and brown V. subterranean.…”
Section: Nutrition Content/health Benefits Of Bambara Nutsmentioning
confidence: 99%
“…Bambara groundnut plays an important role not only in addressing food and nutritional well-being, but also in boosting immunity ( Adebowale et al, 2011 ; Adedayo et al, 2021 ), livestock feed ( Feldman et al, 2019 ), improving biodiversity, and protecting farmers’ livelihoods. Resistant starch is concentrated in this crop, which encourages the slow and sustained release of glucose into the bloodstream, making a healthy diet ( Cummings and Englyst, 1995 ).…”
Section: Mainstreaming Bambara Groundnut For Ensuring Food and Nutritional Securitymentioning
confidence: 99%